Association between stroke and systemic inflammation response index (SIRI): a National Health and Nutrition Examination Survey (NHANES) Study 2015–2020 - Adib Valibeygi; Mohammadreza Fardaei; Sepideh Niknejad (BMJ Neurology Open)
Objectives The present study aimed to compare the relationship between history of stroke and four different inflammatory indices, including high-sensitivity C reactive protein (hsCRP), inflammatory burden index (IBI), neutrophil-to-lymphocyte ratio (NLR), and systemic inflammation response index (SIRI).Methods In this cross-sectional study, data from the National Health and Nutrition Examination Survey from 2015 to 2020 were used, yielding a sample of 25 531 participants. Individuals younger than 20, pregnant women, patients with cancer and missing cases were excluded. Baseline characteristics and inflammatory markers mentioned above were analysed. Logistic regression models assessed the association between inflammatory indices and the history of stroke.Results Of the 7828 eligible cases, 271 (3.4%) had a history of stroke. Stroke was more prevalent among older subjects, smokers, patients with diabetes, hypertension and dyslipidaemia, and those less physically active. All inflammatory indices were elevated considerably in stroke survivors, according to crude analysis. After adjusting for covariates, hsCRP (p=0.519, 95% CI: 0.961 to 1.083), NLR (p=0.125, 95% CI: 0.947 to 1.565) and IBI (p=0.157, 95% CI: 0.991 to 1.060) did not reveal any significant difference between the stroke survivors and control subjects. SIRI was the only inflammatory index significantly associated with a history of stroke (p=0.005, 95% CI: 1.154 to 2.274).Conclusion This study revealed that among the hsCRP, IBI, NLR and SIRI, SIRI is the only one independently associated with a history of stroke. Our findings, in conjunction with the pre-existing evidence from observational and experimental studies, highlight the role of monocytes as a component of SIRI in chronic inflammation, which may induce vascular thrombotic events, including stroke.